The cultural acceptability of insects as food: An empirical study in Cambodia - Franco, Alexander (International Journal of Innovative Research and Scientific Studies, 2025)
This is a pioneering study regarding Cambodia that examined aspects of entomophagy (the consumption of edible insects) in that country. An inferential sample of the undergraduate population of a business college in Phnom Penh was drawn based on convenience sampling. The respondents provided data by answering an anonymous, self-administered questionnaire that contained seven demographic independent variables (gender, year of study, where the respondent was raised - urban vs. rural, religion, socio-economic family status, perceived risk to human health, and prior consumption of edible insects). The questionnaire also contained thirty attitudinal questions measured on Likert scales. The study found that gender was not a significant factor in receptivity to consuming insects. However, year of academic study, where the respondent was raised, religion, socio-economic family status, and perceived risk to human health (a manifestation of food neophobia) all had partial support. The study also found strong support for consuming beef, pork, chicken, and fish from animals that were fed insects as feed. This study contributes to the sparse academic literature on the commercialization of insects as food since the marketing component of any adoption strategy requires knowledge of the degree of receptivity by the different segments of a given population.